0 like 0 dislike
Find the solution for the following system of equations.

y = -2x + 6
y = 3x - 4
by

1 Answer

0 like 0 dislike
when you get this kind of exercise, you find need to find y or x in one of the exactions and fill it in in the other, however in this exercise the two y's are already given so all you need to do is replace the y in one of the exactions with the other exactions like this:

(keep in mind, you need to keep writing both of the exactions over again, otherwise you'll lose an exaction. and we'll need it later on)

y=-2x+6

y=3x-4

y=-2x+6

-2x+6=3x-4

y=-2x+6

-2x-3x=-4-6

y=-2x+6

-5x=-10

y=-2x+6

x= 2

and now replace the x in the first exaction with the x that we found:

y=-2(2)+6

x=2

y=-4+6

x=2

y=2

x=2
by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found